A Feasibility Study on Frents Celyhaus - Duque, Sonia Teresa C. (College of Engineering, 1996)
The product, Frents Celyhaus, is a low cost housing unit built from pre-fabricated monolithic walls, dividers, flooring and roofing. It is a monolithic, lightweight structural system that enables a complete house to be manufactured in the factory or in the job site using locally available materials. It is composed of a panel of styropor, covered with a net meshing with chopped fiberglass strands glued to it using Polyweld. Based on the market study, there is an existing demand for low-cost housing in the country. Targeting the National Capital Region, Regions III and IV, the company can get a yearly market share of 7.4%. Production demand for Frents Celyhaus increases yearly from 35,509 in 1997 to 53,335 in 2003. The technical study showed that there are enough resources in the country available for the production of the Frents Celyhaus housing units. Upon computation of the least production cost for the different manufacturing alternatives of such units and comparing the alternatives presented, the best production alternative is to produce the Styropor panels and fabricate the patented Frents Celyhaus materials in-house at the Export Processing Zone in Rosario Cavite. Projected start-up cost based on the quotations in the technical study showed a figure of P393,024,752 as initial investment. The financial study determined the source of financing that is the GSIS Housing Developers Loan. GSIS loans up to the total project start-up cost with an annual interest rate of 9%. The different ratios in the Income Statement, Cash flow, and Balance Sheets showed that the venture is profitable. It registered an IRR of 83%, much higher than the comparison rate of 20%. Payback period for the business is pegged at 2.38 years. The net present value for the project was also computed to be P150,724,727. A figure very much greater than zero. Net income for 1997 is estimated at P121,260,007. The social profitability study showed that the benefits of the business far outweigh the disbenefits caused by it in the community. Employment and tax contributions of the company as well as the increase in the housing supply are very large. The organization and management study determined the necessary organizational structure to be used by the company. It has the corporate form of ownership so as to ease the burden of capital pooling and getting of loans. The venture has an initial manpower requirement of 251 direct laborers and a management organization of 22 people comprising the positions for general manager down to the foremen. To sum all up, the putting up of the business venture Frents Celyhaus, is very much feasible as shown in the preceding studies.